2019
DOI: 10.3390/f10080659
|View full text |Cite
|
Sign up to set email alerts
|

Non-Targeted Metabolomics Reveals Patterns of Metabolic Changes during Poplar Seed Germination

Abstract: Research Highlights: This study was the first to use metabolomics techniques to investigate seed germination in poplar, a model woody plant. Our results lay a foundation for uncovering changes in metabolite levels during woody plant seed germination and for understanding the underlying mechanism. Background and Objectives: Poplar is a model woody plant. Because poplar can be easily propagated asexually, the molecular mechanism of poplar seed germination has not been well studied. However, long-term asexual rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 40 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…Moreover, TCA-cycle was also significantly down-regulated relative to RPPDS. Non-Targeted metabolomics analysis of Poplar seeds also revealed that three TCA cycle intermediates (citrate, isocitrate and succinate) substantially accumulated during the periods of slow water uptake and then promptly decreased until radicle protrusion (Qu et al, 2019). Research conducted with non-dormant and dormant seeds of Leymus chinensis demonstrated that the proteins involved in TCA cycle were decreased in non-dormant seeds (Hou et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TCA-cycle was also significantly down-regulated relative to RPPDS. Non-Targeted metabolomics analysis of Poplar seeds also revealed that three TCA cycle intermediates (citrate, isocitrate and succinate) substantially accumulated during the periods of slow water uptake and then promptly decreased until radicle protrusion (Qu et al, 2019). Research conducted with non-dormant and dormant seeds of Leymus chinensis demonstrated that the proteins involved in TCA cycle were decreased in non-dormant seeds (Hou et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The changes of seed storage substances during seed germination and pre-sprouting have been discussed in some cereal and legume crops and model woody plant, such as rice, barley, white, mung bean and poplar [6,21,24,32]. The above reports demonstrated that active metabolism processes occurred to provide nutrients and energy reserves for seed germination, but varying metabolite-metabolite links may exist in plant species [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular studies on the imbibed-barley seeds have also shown that genes involved in amino acid metabolism are triggered after imbibitions36. In poplar, the involvement of amino acid metabolism is exclusive between the late stages of embryo water uptake to the completion of seedling growth [21]. To better understand the underlining mechanism during in-situ germination of nut crops, we explored the synergetic roles of metabolites in the nut kernels for regulation of in-situ germination of Carya species nut kernels using a comparative metabolomics approach in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations